PENGGUNAAN METODE PHONETIC DALAM PEMBELAJARAN KOSA KATA BAHASA ARAB - Amirul Mukminin; Khoirul Anwar; M. Budi Amin Amri (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
Some methods are developed and applied in various institutions for improving the quality of student learning outcomes. Likewise, in the Arabic Development Institute (LPBA) Pondok Pesantren Salafiyah Syafi'iyah Sukorejo Situbondo which applies the Phonetic Method in the learning, especially in Arabic vocabulary learning. In the application, 1) teacher prepares a learning tools, 2) the learning is begun by a simple Arabic vocabulary expressions, 3) it is Helped by a classroom equipment as a media aid, and 4) teacher always provides a practical exercises at the end of learning.